2021
DOI: 10.21203/rs.3.rs-239030/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Culture and Coronavirus Disease Statistics Public Health Through the Lens of Hofstede’s Cultural Dimensions, A Multiple Regression Analysis

Abstract: Background Hofstede’s Culture Dimensions (HCD) are the most prevalent metrics with which social scientists distinguish cultural differences between countries. In this study, we examine the relationships between HCD and the COVID-19 pandemic. In particular, we investigate how differences in COVID-19 infection, death and recovery between countries correlate with differences in individualism (IDV), indulgence (IVR) and power distance index (PDI).Method We use multiple linear regressions to interpret statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…The model of Hofstede has already been used in the COVID-19 context by Wang, Bandera et al (2021) Differently, countries like Italy, France and Spain are all characterized by high scores of "Uncertainty avoidance", which means that they are prone to rely on institutions in times of trouble or uncertainties. On the other hand, these three countries are relatively low on "Indulgence", reflecting a more restrictive way to live their lives and the need of following their instincts.…”
Section: Country Analysis According With Hofstede's Cultural Dimensionsmentioning
confidence: 99%
“…The model of Hofstede has already been used in the COVID-19 context by Wang, Bandera et al (2021) Differently, countries like Italy, France and Spain are all characterized by high scores of "Uncertainty avoidance", which means that they are prone to rely on institutions in times of trouble or uncertainties. On the other hand, these three countries are relatively low on "Indulgence", reflecting a more restrictive way to live their lives and the need of following their instincts.…”
Section: Country Analysis According With Hofstede's Cultural Dimensionsmentioning
confidence: 99%
“…Indulgence vs restraint (IVR), yaitu dimensi yang berkaitan dengan tingkat kebebasan masyarakat dalam mengekspresikan keinginan dan rasa perasaannya. Selanjutnya merujuk pada beberapa hasil penelitian terdahulu, dari enam komponen dimensi budaya tersebut di atas (Wang et al, 2021;Huynh, 2020;Gokmen et al, 2021;Gupta et al;, dan Messner (2020 menemukan empat dimensi budaya dengan dinamika Covid-19, meskipun diantara mereka menemukn hasil yang berbeda, yaitu: dimensi PDI, IDV, UAI, dan IVR (Tabel 1). Sementara dimensi MAS dan LTO tidak ditemukan keterhubungannya itu dengan dinamika Covid-19.…”
Section: Pendahuluanunclassified
“…There have been many studies stated these variants in governmental responses are due to the cultural differences between communities (Velamoor & Persad, 2020 [3]; Airhihenbuwa et al, 2020 [4]; Darwin et al, 2021 [5]; Wang, Bandera & Yan, 2021 [6]). For example, Velamoor & Persad, (2020) suggested that countries with a strong political culture of command-and-control governance (Singapore, South Korea, China, Russia, North Korea), tend to use the strategies that apply for all populations, no matter if they like it or not.…”
Section: Literature Review and Hypothesis Development A Literature Re...mentioning
confidence: 99%
“…Culture matters not only the institutional and individual response to a pandemic, but also the outcomes. Wang, Ban-dera & Yan (2021) found the statistical relation between Individualism vs Collectivism (IDV) and death rate. The countries with higher IDV had higher regional mortality rate, which suggests the contribution of the <freedom= mindset but only focused on their own health, not of the others.…”
Section: Literature Review and Hypothesis Development A Literature Re...mentioning
confidence: 99%